Work-Life Conflict Among Higher Education Institution Workers' During COVID-19: A Demands-Resources Approach - Garraio, Carolina; Freitas, Jorge Peixoto; Magalhães, Sara Isabel; Matias, Marisa (Frontiers in Sociology, 2022)
Higher Education Institutions (HEI) workers' were highly impacted by the COVID-19 pandemic, which magnified gender differences in terms of management of work and personal life. Most studies published so far have primarily focused on a group of HEI’s workers (i.e., teachers and researchers), but not on staff members, despite their crucial role for HEI’s functioning. Following the Job Demands-Resources theory, we aimed to: i) characterize work-life conflict (WLC) among men and women workers from an HEI (staff and teachers/researchers) during the COVID-19 pandemic; and ii) explore the major predictors of WLC for both staff and teachers/researchers. This study includes a sample of 262 workers from one Portuguese HEI (n = 128 staff members; n = 134 teachers/researchers) who answered an online survey. An Independent Samples T-Test showed that the reported current WLC was significantly higher for teachers/researchers compared to staff. Moreover, women teachers/researchers showed higher WLC than men. Additionally, using a Repeated Measures ANOVA, we found that the increase in the reported levels of WLC (before the pandemic and currently) was significantly more prominent among teachers/researchers than in the staff group. Regarding the predictors of WLC for both groups separately, a Multiple Hierarchical Linear Regression showed that gender was only a predictor in the case of teachers/researchers. Role overload, conceptualized as a demand, was a predictor for both staff and teachers/researchers. As for potential resources, work dedication negatively predicted WLC for staff, whereas family-friendly organization perceptions predicted less WLC for teachers/researchers. These results highlight the importance of understanding HEIs holistically, by considering workers’ individual characteristics such as gender, but also distinct careers inside the institutions. As most European HEIs are currently making active efforts to promote gender-equal academic workplaces, these findings may help them design tailored and effective measures to address employees’ work-life balance issues, not only considering gender, but also the different types of demands associated with each group of workers within HEIs.